The making of a man notes on transsexuality - Februari, Maxim 1963- (Reaktion Books, 2015)
In the autumn of 2012, Maxim Februari-known until then as writer and philosopher Marjolijn Februari-announced his intention to live as a man. The news was greeted with a diversity of reactions, from curiosity to unease. These responses made it absolutely clear to Februari that most of us don't know how to think about transsexuality. The Making of a Man explores this lacuna through a deeply personal meditation on a profoundly universal aspect of our identities. Februari contemplates the many questions that sexual transitions entail: the clinical effects of testosterone, the alteration of sexual organs, and its effects on sexual intimacy; how transsexuality figures in the law; and how it challenges the way we talk about sex and gender, such as the seemingly minor-but crucially important-difference between the terms "transsexual" and "transgender." He analyzes our impressions of effeminate men and butch women, separating apparent acceptance from actual prejudice, and critically examines the curious requirement in many countries that one must demonstrate a psychological disturbance-a "gender identity disorder"-in order to be granted sex change therapies. From there he explores the seemingly endless minutiae changing genders or sex effect, from the little box with an M or an F on passports to the shockingly sudden way testosterone can adjust physical features. With his characteristically clear voice combined with intimate-sometimes moving, sometimes funny-ruminations, Februari wakes readers up to all the ways, big and small, our world is structured by sex and gender